Association of PEAR1 genetic variants with platelet reactivity in response to dual antiplatelet therapy with aspirin and clopidogrel in the Chinese patient population after percutaneous coronary intervention. Issue 141 (May 2016) - Yao, Yi; Tang, Xiao-fang; Zhang, Jia-hui; He, Chen; Ma, Yuan-liang; Xu, Jing-jing; Song, Ying; Liu, Ru; Meng, Xian-min; Song, Lei; Chen, Jue; Wang, Miao; et al.
Abstract: Introduction: Platelet Endothelial Aggregation Receptor-1 (PEAR1) is a recently reported platelet transmembrane protein which plays an important role in platelet aggregation. The aim of this study was to investigate whether PEAR1 genetic variations were associated with platelet reactivity as assessed by adenosine diphosphate(ADP)-induced platelet aggregation in Chinese patients treated with aspirin and clopidogrel. Methods: Patients with coronary heart disease (CHD) who underwent percutaneous coronary intervention (PCI) were enrolled in the study. All patients were on dual antiplatelet therapy with aspirin and clopidogrel. ADP-induced platelet aggregation was measured by thromboelastography and defined as percent inhibition of platelet aggregation (IPA). Patients ( n  = 204) with IPA < 30% were identified as high on-treatment platelet reactivity (HPR). Patients ( n  = 201) with IPA > 70% were identified as low on-treatment platelet reactivity (LPR). Sixteen single nucleotide polymorphisms (SNPs) of PEAR1 were determined by a method of improved multiple ligase detection reaction. Results: Among the 16 SNPs examined by univariate analysis, 5 SNPs were significantly associated with ADP-induced platelet aggregation. Minor allele C at rs11264580 ( p  = 0.033), minor allele G at rs2644592 ( p  = 0.048), minor allele T at rs3737224 ( p  = 0.033) and minor allele T at rs41273215 ( p  = 0.025) were strongly associated with HPR, whereas homozygous TT genotype at rs57731889 ( p  = 0.009) was associated with LPR. Multivariate logistic regression analysis further revealed that the minor allele T at rs41273215 ( p  = 0.038) was an independent predictor of HPR and the homozygous TT genotype at rs57731889 ( p  = 0.003) was an independent predictor of LPR. Conclusions: PEAR1 genetic variations were strongly associated with ADP-induced platelet aggregation in Chinese patients with CHD treated with aspirin and clopidogrel. These genetic variations may contribute to the variability in platelet function. The utility of PEAR1 genetic variants in the assessment and prediction of cardiovascular risk warrants further investigation. Highlights: PEAR1 polymorphisms are related to ADP induced on-treatment platelet reactivity. Newly identified SNP rs57731889 of PEAR1 associated with low platelet reactivity. Changes at different sites of PEAR1 gene differentially affect platelet reactivity.